Comunication Strategy of Smiling West Java Ambassador Program using SWOT Analysis and QSPM - Sy, Imaddudin (Telangke:Jurnal Telangke Ilmu Komunikasi, 2025)
Exposing tourism potential in West Java needs to be developed through the standardization of priority tourism destination promotion. The West Java Smile Ambassador (SWJ) program, involving 108 content creators, implements tourism marketing policies by referring to the mission of the West Java province to become a province with Champion tourism. This research method uses qualitative and quantitative approaches, through SWOT analysis and measurement of strategy results with QSPM, to provide strategic recommendations in product and market development. The study results show internal and external factors based on the IE matrix; communication in the SWJ Ambassador program generally uses the Growth and Build strategy with a focus on product and market development. The results of the grand strategy show diversification that suggests the use of long-term strengths by sustainably adding innovative programs so that it is not monotonous by only creating creative content, and involving the wider community, not only content creators. However, it can communicate with tourism destination managers in West Java directly